Project Based Learning: Upaya Menumbuhkan Jiwa Entrepeneurship Siswa pada Pembelajaran Prakarya dan Kewirausahaan - Mir'atil Isnaini; Cici Yulihendri; Dina Aulia; Wyanet Putri Alisha; Susi Evanita; Friyatmi (Universitas Negeri Padang, 2023)
This study aims to describe the project based learning strategy as an effort to foster students’ entrepreneurial interest in entrepreneurship learning at SMAN 3 Batam. The data collections method uses non-participant observations, interviews, and documentation. The results showed that cultivating the entrepreneurial spirit of students, was carried out in the form of cheerful Saturday Activities, direct selling, and involving students in entrepreneurship compettions. The goal is to stimulate students to be actively involved in these activities, so that they have an impact on students that is how important entrepreneurship is in life. In this activity, the school petrified the procurement of facilities and insfrastructure needed by students, so that the purpose of holding cheerful Saturday Activities, direct selling, and entrepreneurship competitions that were participated in could be achieved.